2023
DOI: 10.1111/joim.13699
|View full text |Cite
|
Sign up to set email alerts
|

Neurobiology of eating behavior, nutrition, and health

Abstract: Eating behavior and food‐related decision making are among the most complex of the motivated behaviors, and understanding the neurobiology of eating behavior, and its developmental dynamics, is critical to advancing the nutritional sciences and public health. Recent advances from both human and animal studies are revealing that individual capacity to make health‐promoting food decisions varies based on biological and physiological variation in the signaling pathways that regulate the homeostatic, hedonic, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 180 publications
0
3
0
Order By: Relevance
“…Eating behavior is a complicated process which involves interactions between physiological variables and the food environment [ 8 ]. Eating behavior refers not only to the foods consumed, the nutrients consumed, or the process of eating, but also to food preferences, choices, and consumption patterns [ 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…Eating behavior is a complicated process which involves interactions between physiological variables and the food environment [ 8 ]. Eating behavior refers not only to the foods consumed, the nutrients consumed, or the process of eating, but also to food preferences, choices, and consumption patterns [ 9 ].…”
Section: Introductionmentioning
confidence: 99%
“… 30 Another randomised trial reported that 4 weeks of probiotic supplementary powder containing Bifidobacteria and Lactobacillae resulted in changes in microbial genera abundance that correlated with improvements of emotional attention and memory, paralleled by differences in related brain activation. 31 Our findings now present prebiotics-induced changes in brain activation with potential implications for food craving and decision-making: While the neuronal processes underlying human eating behaviour are far from fully understood, 32 neuroimaging studies indicate neural responses within VTA and OFC to underly dopamine-related reward anticipation and subjective value attribution of food, respectively, linking stronger BOLD-related activation to higher reward values and decision-making. 33 Indeed, midbrain and medial OFC activation during fMRI in response to milkshake taste predicted the amount of milkshake intake after the scan.…”
Section: Discussionmentioning
confidence: 75%
“…Evidence also suggests that the caudate nucleus plays a key role in mediating external stimuli and internal preferences to guide behavior (Doi et al, 2020). The hypothalamus is integral to stress responses and homeostatic regulation of caloric intake to meet real and perceived nutrition needs (Gupta et al, 2020; Stover et al, 2023). Dysfunction in these areas is progressive with eating and drug use, resulting in altered reward processing and a shift in ‘liking’ vs. ‘wanting’ the hyper-fixated substance (Bodell et al, 2023; Morales, 2022; Morales & Berridge, 2020).…”
Section: Discussionmentioning
confidence: 99%